Frontiers of Ferroptosis in Cancer Treatment - Malik, Durr-e-shahwar; Romero, Mirna Azalea; Halim, Saiyada Fatima Maida; Elsori, Deena; Youssef, Lara; Yulaevna, Ishmuratova Margarita; Sabitaliyevich, Uteuliyev Yerzhan; Attar, Rukset (Cellular and Molecular Biology, 2022)
Recent phenomenal advancements in genomic and proteomic technologies and rapid breakthroughs in the interpretation of large gene expression datasets have enabled scientists to comprehensively characterize the gene signatures involved in ferroptosis. Ferroptosis is an iron-dependent form of non-apoptotic cell death that has gained the worthwhile attention of both basic and clinical researchers. Ferroptosis has dichotomous, context-dependent functions both as a tumor suppressor and promoter of carcinogenesis. Essentially, pharmacological modulation of ferroptosis by its induction as well as its inhibition holds enormous potential to overcome drug resistance and to improve the therapeutic potential of chemotherapeutic drugs in a wide variety of cancers.